Identification and Characterization of Pathogenic Fungi Causing Necrosis in Vigna unguiculata - Afiya, Dina; Mustofa, Ali; Nurtjahyani, Supiana Dian (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Vigna unguiculata (cowpea) is an important legume crop whose productivity can be affected by foliar diseases, including leaf necrosis caused by fungal pathogens. Identification of fungi associated with necrotic symptoms is essential as baseline information for plant disease management. Methods: This study aimed to identify fungi associated with necrotic lesions on cowpea leaves. Leaf samples showing necrotic symptoms were collected from agricultural fields in Tengger Wetan Village, Kerek Subdistrict, Tuban Regency, East Java. Fungal isolation was performed from infected leaf tissues to obtain pure cultures. Identification was conducted based on macroscopic colony characteristics and microscopic features using slide culture techniques and standard morphological identification keys. Results: Two dominant fungal isolates were consistently associated with necrotic symptoms on cowpea leaves. These fungi were identified morphologically as Alternaria alternata (isolate D1) and Nigrospora sp. (isolate D3). A. alternata was characterized by yellowish-white colonies, hyaline septate hyphae, and dark oval conidia, whereas Nigrospora sp. exhibited cottony white colonies with brown, globose conidia. Both fungi were associated with brown to black necrotic spots on the leaf surface. Conclusions: The findings provide initial information on fungal species associated with leaf necrosis in cowpea based on morphological identification. This information is useful as a foundation for further pathological and molecular studies to confirm species identity and support the development of appropriate disease management strategies.